Measurement of temperature of a dusty plasma from its configuration. Issue 4 (29th January 2020) - Mukherjee, Rupak; Jaiswal, Surabhi; Shukla, Manish K.; Hakim, Ammar; Thomas, Edward
Abstract: A new concept called "configurational temperature" is introduced in the context of dusty plasma, where the temperature of the dust particles submerged in the plasma can be measured directly from the positional information of the individual dust particles and the interaction potential between the dust grains. This method does not require the velocity information of individual particles, which is a key parameter to measure the dust temperature in the conventional method. The technique is initially tested using two‐dimensional (2D) OpenMP parallel molecular dynamics and Monte Carlo simulation and then compared with the temperature evaluated from experimental data. The experiment have been carried out in the Dusty Plasma Experimental (DPEx) device, where a 2D stationary plasma crystal of melamine formaldehyde particles is formed in the cathode sheath of a DC glow discharge argon plasma. The kinetic temperature of the dust is calculated using the standard particle image velocimetry technique at different pressures. An extended simulation result for the three‐dimensional case is also presented, which can be employed for the temperature measurement of a three‐dimensional dust crystal in laboratory devices.